2015
DOI: 10.1007/s13196-015-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Basic properties and nanostructure of wood from four fast growing species from a community forest

Abstract: Four fast-growing wood species, jabon (Anthocephalus cadamba), lento-lento (Arthrophyllum diversifolium), acacia (Acacia mangium) and pulai (Alstonia spp.), can be easily found in many areas of the South Sulawesi Community Forest. This research evaluates basic properties (physical, mechanical and chemical) and nanostructure of the woods of each species. Physical and mechanical properties were analyzed according to SNI 03-6847-2002 and ASTM D 143-2005, while the chemical components were analyzed according to TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Analisis kadar PK dilakukan dengan cara menimbang sampel ± 1 g, 0,3 g dan 0,4 g katalisator selenium reagent mixture (pottasium sulfat + cupri --------------------------------( ----------------------------- Khoshnevisan et al (2011) melaporkan menyatakan struktur substrat dapat mempengaruhi produksi enzim, sehingga dapat menurunkan atau meningkatkan efisiensi aktivitasnya. Yunianti et al (2015) melaporkan kerapatan dinding sel meningkat sejalan dengan meningkatnya kandungan selulosa dan derajat kristalinitas selulosa.…”
Section: Fermentasi Sabut Kelapaunclassified
“…Analisis kadar PK dilakukan dengan cara menimbang sampel ± 1 g, 0,3 g dan 0,4 g katalisator selenium reagent mixture (pottasium sulfat + cupri --------------------------------( ----------------------------- Khoshnevisan et al (2011) melaporkan menyatakan struktur substrat dapat mempengaruhi produksi enzim, sehingga dapat menurunkan atau meningkatkan efisiensi aktivitasnya. Yunianti et al (2015) melaporkan kerapatan dinding sel meningkat sejalan dengan meningkatnya kandungan selulosa dan derajat kristalinitas selulosa.…”
Section: Fermentasi Sabut Kelapaunclassified
“…The changes in MOE were closely related to changes in material properties of the wood. Previous studies have explained that heat treatment at < 160°C increased bending strength (Kocaefe et al 2010), Amin and Dwianto (2006) found that the highest temperature used resulted in decrease in fibre walls and increase in wood crystallinity, while Yunianti (2012) identified that a certain amount of crystallinity and MOE had a very high correlation ( r = 0.83).…”
Section: Resultsmentioning
confidence: 96%